Low Detection Limit and High Sensitivity Wind Speed Sensor Based on Triboelectrification‐Induced Electroluminescence - Li Su; Hailu Wang; Zhen Tian; Haojie Wang; Qian Cheng; Wei Yu (Advanced Science, 2019)
Abstract The rapid development of the Internet of Things (IoT) has tremendously increased the demands for wind speed sensors in various applications, such as weather forecasting and environmental monitoring. To date, many wind speed sensors are developed based on triboelectric nanogenerators (TENGs). However, the low output current leads to a poor sensing precision, which greatly limits their practical applications. Here, a wind speed sensor is proposed by integrating a wind‐driven triboelectrification‐induced electroluminescence (TIEL) component with a perovskite‐based photodetector (PD) for enlarged electric current output. Compared with mechanoluminescence (ML), TIEL displays significantly higher signal intensity even under gentle breezes. In addition, the emission peak of TIEL matches with the absorption band of perovskite materials. Thus, TIEL materials are promising candidates for generating distinct electrical signals in real‐time to facilitate the detection of wind speed. With a comparable detection limit (5 m s−1) to a conventional TENG‐based wind speed sensor, the sensitivity of this hybrid sensor is three magnitudes higher at low bias voltages and, the response time is extremely short (<0.3 s). Moreover, it shows a favorable correlation with a commercial sensor. This research provides important progress toward environmentally‐friendly light sources and TIEL‐related sensor systems.